Androgen and oestrogen receptors as potential prognostic markers for patients with ductal carcinoma in situ treated with surgery and radiotherapy. Issue 5 (28th November 2017) - Ravaioli, Sara; Tumedei, Maria Maddalena; Foca, Flavia; Maltoni, Roberta; Rocca, Andrea; Massa, Ilaria; Pietri, Elisabetta; Bravaccini, Sara
Summary: Ductal carcinoma in situ (DCIS) is a heterogeneous disease that has been investigated less extensively than invasive breast cancer. Women with DCIS are mainly treated with conservative surgery almost exclusively followed by radiotherapy. However, as radiation treatment is not always effective, the search for biomarkers capable of identifying DCIS lesions that could progress to invasive cancer is ongoing. Although conventional biomarkers have been thoroughly studied in invasive tumours, little is known about the role played by androgen receptor (AR), widely expressed in DCIS. A series of 42 DCIS patients treated with quadrantectomy and radiotherapy were followed for a period of up to 95 months. Of these, 11 had recurrent DCIS or progressed to invasive cancer. All tumours were analysed for clinical pathological features. Conventional biomarkers and androgen receptor expression were determined by immunohistochemistry. Our results showed that AR was higher in tumours of relapsed patients than non‐relapsed patients ( P value: 0.0005). Conversely, oestrogen receptor (ER) was higher, albeit not significantly, in non‐relapsed patients than in relapsed patients. AR/ER ratio was considerably different in the two subgroups ( P value: 0.0033). Area under the curve (AUC) values were 0.85 for AR and 0.80 for the AR/ER ratio. These preliminary results highlight the potentially important role of both AR and the AR/ER ratio as prognostic markers in DCIS.